2016
DOI: 10.1016/j.molcel.2016.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Ctf4 Links DNA Replication with Sister Chromatid Cohesion Establishment by Recruiting the Chl1 Helicase to the Replisome

Abstract: SummaryDNA replication during S phase is accompanied by establishment of sister chromatid cohesion to ensure faithful chromosome segregation. The Eco1 acetyltransferase, helped by factors including Ctf4 and Chl1, concomitantly acetylates the chromosomal cohesin complex to stabilize its cohesive links. Here we show that Ctf4 recruits the Chl1 helicase to the replisome via a conserved interaction motif that Chl1 shares with GINS and polymerase α. We visualize recruitment by EM analysis of a reconstituted Chl1-Ct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
176
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(190 citation statements)
references
References 51 publications
12
176
2
Order By: Relevance
“…The human Ctf4 homolog AND-1 shows additional interactions with Pol δ (142). Other replication proteins, such as Dna2 and the sister chromatin cohesion protein Chl1, also bind Ctf4, marking this factor as an important interaction hub within the replisome (141, 143). Surprisingly, a deletion of CTF4 , or of the S. pombe homolog mcl1 + , is viable.…”
Section: Replisome Coordinationmentioning
confidence: 99%
“…The human Ctf4 homolog AND-1 shows additional interactions with Pol δ (142). Other replication proteins, such as Dna2 and the sister chromatin cohesion protein Chl1, also bind Ctf4, marking this factor as an important interaction hub within the replisome (141, 143). Surprisingly, a deletion of CTF4 , or of the S. pombe homolog mcl1 + , is viable.…”
Section: Replisome Coordinationmentioning
confidence: 99%
“…Mutants in many replication fork-associated cohesion factors show reduced acetylated Smc3 in budding yeast [13-15]. This observation can be explained by a multitude of mechanisms, including defects in cell cycle, altered residence time of cohesin on chromatin, and/or reduced accessibility of the Eco1 acetyltransferase to cohesin.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that cohesin colocalizes with replication forks in budding yeast [68] and is recruited to replication forks in Xenopus egg extracts and human cells [69,70]. In addition, cohesin also interacts with the fork-associated Chl1 helicase [71]. Surprisingly, and in contrast to ctf18 and chl4 , the RPA mutation did not suppress the cohesion defect of the chl1 mutant.…”
Section: Implications For Sister Chromatid Cohesionmentioning
confidence: 99%